The Toxicity of Silver Nanoparticles (AgNPs) to Three Freshwater Invertebrates With Different Life Strategies: Hydra vulgaris, Daphnia carinata, and Paratya australiensis - Lekamge, Sam; Miranda, Ana F.; Abraham, Amanda; Li, Vivian; Shukla, Ravi; Bansal, Vipul; Nugegoda, Dayanthi (Frontiers in Environmental Science, 2018)
The toxicity of manufactured nanoparticles varies greatly depending on the test species in consideration and estimates of toxicity may also be confounded by test media in which the organisms are cultured. For a more comprehensive toxicity evaluation, species at different trophic levels or with life strategies, tested in different media should be included. In this study, we examined the toxicity of tyrosine-coated silver nanonparticles (tyr-AgNP) to three Australian freshwater invertebrates: Hydra vulgaris, Daphnia carinata, and Paratya australiensis. Tyr-AgNPs were synthesized, characterized and their behavior was examined in different media used for acute toxicity tests. Additionally, the sensitivity of tested organisms to tyr-AgNPs was compared to ionic silver (Ag+). Based on the LC50 values of both tyr-AgNPs and Ag+ ions at different time points, D. carinata was found to be the most sensitive species followed by P. australiensis and H. vulgaris. NP stability studies revealed that tyr-AgNPs were least stable in hydra medium followed by daphnid and shrimp media. This study demonstrates that significant differences in NP toxicity to aquatic organisms exist and the test media and the life strategy of the species play a key role in these differences. Therefore, it is recommended that a multispecies approach is used in predictive risk assessment of NPs and to ensure protection of native species from possible toxic effects from NPs released into aquatic systems. Also recommended is to carefully investigate the fate and behavior of NPs in different media in assessing NP toxicity and emphasize the need to use native species in developing relevant regulatory frameworks.